System of Regular Remedial Measures in the Administrative Procedure in the Czech Republic and Other Countries of the So-Called V4 - Potešil, Lukáš (Public Governance, Administration and Finances Law Review, 2016)
This article focuses on the system of standard (ordinary) remedial measures used in the administrative procedure that can be found in the Administrative Procedure Acts of so called Visegrad Four (Central European) countries. Mentioned is not only the national legislation but also European impact in this sphere and connecting roots. It can be found some problems that are typical for Visegrad Four countries like ‘remonstrance’. This paper tries to show possible ways to solve such problems and to emphasize that there is still number of national specifics which can be found. These can be understood as ‘inspirational designs’, whether positive or negative.